2015
DOI: 10.1002/mren.201500008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Viscoelastic Behavior of Low‐Density Polyethylene Produced in High‐Pressure Tubular Reactors

Abstract: In the open literature, there is a lack of comprehensive predictive models that can provide detailed information on the distributed molecular properties of LDPE (e.g bivariate molecular weight-long-chain distribution, seniority-priority long-chain branching distributions, etc.) produced in a high-pressure process. To address this problem, Meimaroglou and Kiparissides (2010) developed a novel kinetic-molecular topology Monte Carlo (MC) algorithm to predict the exact molecular architecture of nonlinear polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Therefore, a higher processing temperature induces a higher stress relaxation rate of polymer chains, resulting in a decrease of the swelling ratio. As a branched polymer melt possesses a higher activation energy than its linear counterpart, [83] the temperature effect on extrudate swell is related to the molecular thus material parameters as covered in the following subsection. Indeed, Liang et al [33,65,66] found that an increasing processing temperature decreased the extrudate swelling at a given shear stress for polymer melts.…”
Section: Effect Of Processing Parametersmentioning
confidence: 99%
“…Therefore, a higher processing temperature induces a higher stress relaxation rate of polymer chains, resulting in a decrease of the swelling ratio. As a branched polymer melt possesses a higher activation energy than its linear counterpart, [83] the temperature effect on extrudate swell is related to the molecular thus material parameters as covered in the following subsection. Indeed, Liang et al [33,65,66] found that an increasing processing temperature decreased the extrudate swelling at a given shear stress for polymer melts.…”
Section: Effect Of Processing Parametersmentioning
confidence: 99%
“…As a result, a little less than 2000 branched chains were extracted and transferred in a polyconf.dat file. The number of molecules is quite lower than that reported by Pladis et al., [ 24 ] so the BoB‐rheology calculations were performed for the plural polyconf.dat files generated by repeating the MC simulation several times for one condition, and the averaged values thereof were used. The polymer molecules with a degree of polymerization larger than 500 000 (molecular weight 14 × 10 6 ) generated in the MC simulation were excluded as they are practically considered to be a gel.…”
Section: Methodsmentioning
confidence: 99%
“…One of the key components of this relationship is the connection between the synthesis conditions and the bivariate MWD-LCBD of the polymer. The latter is an input to advanced rheological models that can predict the melt flow properties of the resin (Pladis et al, 2015).…”
Section: Modeling Of Bivariate Distributions In Polymer Systemsmentioning
confidence: 99%